Um estudo da influência do cinismo e do materialismo no comportamento de consumo ecologicamente consciente - Casasola, Fernanda Pase (2012)
Environmental degradation and the possibility of natural resource reserve depletion, issues identified as a result economic and productive forces, have caused the rise and strengthening of pro-environmental movements. The environmentally conscious consumer, engaged to these movements, expresses concern in their environmental attitudes and hence in their buying behavior. The individual begins to search for products they believe cause less impact to the environment and value those whose inputs and processes come from environmentally responsible companies. The new consumption patterns become a central theme in a large number of researches that seek to explain and investigate the major changes in consumer behavior. The perception that the adoption of strategies aimed at these consumers is effective, leading to an increase in the number of false promises, which then lead consumers to be influenced by cynicism, questioning the legitimacy of the environmental problem. Still, social and cultural pressure for higher levels of consumption implies lower adoption of environmentally conscious behaviors, influencing the level of consumer materialism. The present study aims to investigate the impact of different variables on the adoption of environmentally conscious consumer behavior. Therefore, the adoption of this behavior was investigated from model based on the study by Cardigo (2008), who adapted the models of Roberts (1996) and Straughan and Roberts (1999). A survey was conducted on 334 respondents, among them students and employees of the Universidade Federal de Santa Maria. The main technique of data analysis was to Structural Equation Modeling. The model adapted from Cardigo (2008) was adequate in understanding the impact of cynicism and materialism on the environmentally conscious consumer behavior and showed good fit indexes in Confirmatory Factor Analysis. Of the ten proposed hypotheses, five were confirmed: materialism has a negative relationship with the environmentally conscious behavior. Furthermore, consumer perceived altruism and efficiency have power to moderate the relationship among cynicism, materialism, environmental concern and environmentally conscious consumer behavior.